Proceedings of the First Multidiscipline International Conference, MIC 2021, October 30 2021, Jakarta, Indonesia 2022
DOI: 10.4108/eai.30-10-2021.2315826
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Micro, Small and Medium Enterprise in West Java Province

Abstract: In 2019, micro, small, and medium enterprises (MSMEs) in West Java contributed 13.24% to national economic growth. This has a positive impact on poverty reduction and employment. Given the importance of MSMEs, a study was conducted to analyze the influencing factors of the growth of MSMEs. The research method used in this study is the ordinary least square with multiple linear regression on the data panel. The independent variables are infrastructure, MSMEs investment growth, gender empowerment index, and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…This finding suggests that SMEs that are innovative and adopt new technologies and business practices are more likely to succeed in their business ventures. This finding is consistent with previous studies that have shown that innovation can enhance productivity, competitiveness, and profitability, which are critical for SME growth [30]- [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding suggests that SMEs that are innovative and adopt new technologies and business practices are more likely to succeed in their business ventures. This finding is consistent with previous studies that have shown that innovation can enhance productivity, competitiveness, and profitability, which are critical for SME growth [30]- [33].…”
Section: Discussionsupporting
confidence: 93%
“…Research by [33], [38] found that market competition has a significant positive effect on the growth of SMEs in West Java Province. The study found that SMEs that faced higher levels of competition had higher levels of business performance and were more likely to invest in innovation than SMEs that faced lower levels of competition.…”
Section: Market Competitionmentioning
confidence: 99%
“…Usaha Mikro kecil dan menengah (UMKM) merupakan kontributor yang signifikan bagi perekonomian Indonesia, mempekerjakan 7,9 juta orang dan memberikan kontribusi 27% terhadap PDB (Aminullah et al, 2022;Supandi, Astuti, et al, 2022). Namun, UMKM di Indonesia menghadapi tantangan dalam memperoleh kredit dan akses keuangan yang terbatas (HANGGRAENI & SINAMO, 2021; Nareswari et al, 2023).…”
Section: Pendahuluanunclassified
“…ensure that every citizen has a job, receives fair wages, and is treated fairly in the workplace; make changes in accordance with different administrative angles connected with arrangement, reinforcing, and security for cooperatives and UMK-M as well as public ventures; working with and speeding up public key tasks in light of public science and innovation and directed by the Pancasila philosophy, as well as making acclimations to different administrative viewpoints connected with further developing the venture biological system. [5] The practice of altering and/or repealing multiple statutory regulations is known as "omnibus law," and its goal is to simplify (simplify) statutory regulations. Countries with common law and the Anglo Saxon legal system developed this approach.…”
Section: Introductionmentioning
confidence: 99%